2004
DOI: 10.5713/ajas.2004.1266
|View full text |Cite
|
Sign up to set email alerts
|

Relative Availability of Iron in Mined Humic Substances for Weanling Pigs

Abstract: Humic substances include several biological active and inactive compounds that are commonly used for improving soil fertility. Use of humic substances in swine diets is a novel concept. Humic substances contain 8,700 mg/kg of iron but its bioavailability is unknown. This study was conducted to test the bioavailability of iron in humic substances for nursery pigs. One hundred twenty five pigs (Newsham, Colorado Springs, CO) were not given supplemental iron while nursing for 21 d. Pigs were weaned on d 21 and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Based on these values and results, the results with respect to chemical composition, mineral contents and colour characteristics of breast and thigh meats suggest that humic acid at the tested doses did not affect on CIE lightness values as follows: lighter (pale) or darker (dark) than normal, but slightly increased L* and a* values of these meats and did not affect b* value. In the present study, the enhanced Fe content of the meats may explain the fact that the humic acid particles and/or minerals from HS preparations may be absorbed (Visser, 1973; Fuchs et al., 1990; Büsing et al., 2005) and the HS can replace FeSO 4 as an alternative iron source for animals, including pigs (Kim et al., 2004; Ji et al., 2006), because the relative bioavailability of the iron in HS has been reported as 71% of iron sulphate (Kim et al., 2004). Thus, our result with regard to a* values was clearly due to differences in Fe content of breast and thigh meats.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Based on these values and results, the results with respect to chemical composition, mineral contents and colour characteristics of breast and thigh meats suggest that humic acid at the tested doses did not affect on CIE lightness values as follows: lighter (pale) or darker (dark) than normal, but slightly increased L* and a* values of these meats and did not affect b* value. In the present study, the enhanced Fe content of the meats may explain the fact that the humic acid particles and/or minerals from HS preparations may be absorbed (Visser, 1973; Fuchs et al., 1990; Büsing et al., 2005) and the HS can replace FeSO 4 as an alternative iron source for animals, including pigs (Kim et al., 2004; Ji et al., 2006), because the relative bioavailability of the iron in HS has been reported as 71% of iron sulphate (Kim et al., 2004). Thus, our result with regard to a* values was clearly due to differences in Fe content of breast and thigh meats.…”
Section: Discussionmentioning
confidence: 72%
“…(2006) reported that there was a trend for reduction in the serum concentrations of Ca, Mg, Fe and P by humic acid, contrary to the augmentation in the meat concentrations of Ca, Fe and Cu at the higher level of humic acid offered in this study. Such a case may be due to a metal chelating effects of humic, which is affected by large number of carboxylic acid side chains (Peña‐Mèndez et al., 2005; Rath et al., 2006) and the mineral content of HS used in the present study (Kim et al., 2004; Ji et al., 2006).…”
Section: Discussionmentioning
confidence: 96%
“…The present study found no significant effect of ZnO and HNa treatment on blood cells, haematocrit and haemoglobin. Rupic et al (1998) reported that inorganic Zn in the diet of fattening pigs appears to be responsible for the increase in the values of erythrocytes, haemoglobin and haematocrit and Kim et al (2004) observed significantly increased erythrocyte values in pigs supplemented with HS. We observed non-significantly higher erythrocytes and haematocrit in ZnO2.5 and HNa + ZnO1.7 as well as non-significantly higher haemoglobin levels in the ZnO2.5 group after three weeks of treatment.…”
Section: Haematological and Serum Biochemical Profilementioning
confidence: 99%
“…The RBV of FSBM to PP was 99.1% when the 3-wk period was considered, and there was no difference in growth response between FSBM and PP. A slope-ratio assay is an effective method to compare RBV of nutrients from different sources (Hahn et al, 1990;Kim and Easter, 2001;DeRouchey et al, 2002;Kim et al, 2004). In this experiment, 3.7% PP was replaced by 4.9% FSBM, with the addition of Lys, Thr, Met, and Trp to match AA profiles.…”
Section: CDmentioning
confidence: 99%